Modifications in magnetic anisotropy of M-type strontium hexaferrite crystals by swift heavy ion irradiation - Kaur, Balwinder; Bhat, Monita; Licci, F.; Kumar, Ravi; Kulkarni, S. D.; Joy, Pattayil Alias; Bamzai, K. K.; Kotru, P. N. (Journal of Magnetism and Magnetic Materials, 2006)
Using vibrating sample magnetometery (VSM) 50 MeV Li(3+) ion irradiation effects on magnetic properties of single crystals of SrGa(x)In(y)Fe(12-(x+y))O(19) (where x = 0, 5, 7, 9; y = 0, 0.8, 1.3, 1.0), are reported. The substitution of Ga and In in strontium hexaferrite crystals decreases the value of magnetization sharply, which is attributed to shifting of collinear magnetic order to a non-collinear one. Reduction of magnetization is also explained to be as a result of the occupation of the crystallographic sites of Fe(3+) by Ga(3+) and In(3+). The Li(3+) ion irradiation decreases the value of magnetization, irrespective of whether the crystals are Ga-In substituted or unsubstituted crystals of SrFe(12)O(19). The result is interpreted in terms of the occurrence of a paramagnetic doublet in crystals replacing magnetic sextuplet as a result of irradiation. Substitution of Ga-In in Strontium hexaferrite decreases the value of anisotropy constant. Irradiation with Li(3+) ions increases the values of anisotropy field for both substituted as well as unsubstituted crystals. Substitution with Ga-In also decreases the Curie temperature (T(c)) but the irradiation with Li(3+) ions does not affect the curie temperature of either Ga-In substituted or pure SrFe(12)O(19) crystals. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: anisotropy field; Curie temperature; irradiation; Magnetic anisotropy; Magnetization

Effect of cation distribution on structural and magnetic properties of Dy substituted magnesium ferrite - Bamzai, K. K.; Kour, Gurbinder; Kaur, Balwinder; Kulkarni, S. D. (Journal of Magnetism and Magnetic Materials, 2013)
Magnesium ferrite and dysprosium (Dy3+) substituted with composition MgDyxFe2-xO4 (x = 0.00-0.07) was prepared by solid state reaction technique. Spinel phase formation was identified using x-ray diffraction technique, thus establishing the cubic spinel symmetry. The morphology was seen through scanning electron microscopic technique, from where the grain size was calculated using average intercept line method. The elemental composition of pure and dysprosium substituted magnesium ferrite was calculated from energy dispersive x-ray analysis spectrum which is then correlated with the experimentally obtained values. Magnetic hysteresis loop of the various compositions establishes it to be soft ferrimagnetic material. The magnetic parameters such as saturation magnetization, coercivity, and retentivity were also calculated. Temperature dependence of saturation magnetization was done to find the Curie temperature of different compositions. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Cation distribution; Curie temperature; Electron microscopy; Magnetization; Spinel ferrite